(untitled) (Research, Society and Development, 2021)
Beans are one of the most produced foods in the entire national territory, with an intense search for productive cultivars with good culinary characteristics. In view of the growing concern of consumers with the diet, the positive implications of functional foods for health and the benefits of beans for the organism, the objective of this study was to verify the content of bioactive compounds and the antioxidant capacity of eight common bean cultivars. cowpea, before and after cooking, as well as in their respective broths. From the samples, the concentrations of ascorbic acid, chlorophyll, carotenoids, anthocyanins, flavonoids, phenolic compounds and antioxidant capacity were determined, and the data obtained were compared using the Tukey test at the 5% probability level. As a result, it was observed that the cultivar Costela de Vaca had the highest concentrations of chlorophyll and carotenoids before and after cooking. There was an increase in the concentration of flavonoids and a reduction in the ascorbic acid content after cooking in all evaluated cultivars. The cultivar BRS Marataoã showed the highest concentration of phenolic compounds in the raw grain and, consequently, the highest antioxidant capacity, however with reduced activity after cooking. For cooking broths, BRS Marataoã and Costela de Vaca were the ones that had the greatest capacity to fight free radicals. Although cooking caused changes in the concentrations of bioactive compounds, the cultivars remained with important functional characteristics, recommending the consumption of green cowpea with cooking broth for greater retention of compounds with antioxidant properties.